Participation In Crimal Acts According In Islamic Criminal Law - Ilham, Muhammad; Nasution, Suherman (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2022)
The current Research This research aims to explore the views of Islamic criminal law in relation to the the concept of participation in a criminal offense. The research method used is a literature study to collect information from various reliable sources. sources. The results show that the concept of participation in criminal offenses according to Islamic criminal law has differences with the concept in Islamic criminal law. criminal offense according to Islamic criminal law has differences with the concept in general criminal law. general criminal law. This research is expected to provide a deeper understanding of understanding of the concept of participation in criminal offenses according to Islamic criminal law so that it can contribute to the development of the criminal system. Islamic criminal law so that it can contribute to the development of a better legal system. system so that it can contribute to the development of a better legal system. After exploring the view of Islamic criminal law related to the concept of participation in criminal offenses, it can be concluded that Islamic criminal law pays special attention to the concept of participation in criminal offenses. that Islamic criminal law pays special attention to the concept of justice, proportion of punishment, as well as consideration of special cases in determining criminal responsibility. criminal responsibility. This indicates that an in-depth understanding of the concept of participation in criminal offenses according to Islamic criminal law can help in improving the legal system. can help in perfecting the existing criminal law system, and can provide a strong foundation for the enforcement of justice. provide a strong foundation for the enforcement of justice in society. It is hoped that the results of this research can make a significant contribution to the development of Islamic criminal law and the legal system as a whole. development of Islamic criminal law and the legal system as a whole.